Dissemination and loss of a biofilm‐related genomic island in marine Pseudoalteromonas mediated by integrative and conjugative elements. (8th November 2017) - Wang, Pengxia; Zeng, Zhenshun; Wang, Weiquan; Wen, Zhongling; Li, Jie; Wang, Xiaoxue
Summary: Acquisition of genomic islands (GIs) plays a central role in the diversification and adaptation of bacteria. Some GIs can be mobilized in trans by integrative and conjugative elements (ICEs) or conjugative plasmids if the GIs carry specific transfer‐related sequences. However, the transfer mechanism of GIs lacking such elements remains largely unexplored. Here, we investigated the transmissibility of a GI found in a coral‐associated marine bacterium. This GI does not carry genes with transfer functions, but it carries four genes required for robust biofilm formation. Notably, this GI is inserted in the integration site for SXT/R391 ICEs. We demonstrated that acquisition of an SXT/R391 ICE results in either a tandem GI/ICE arrangement or the complete displacement of the GI. The GI displacement by the ICE greatly reduces biofilm formation. In contrast, the tandem integration of the ICE with the GI in cis allows the GI to hijack the transfer machinery of the ICE to excise, transfer and re‐integrate into a new host. Collectively, our findings reveal that the integration of an ICE into a GI integration site enables rapid genome dynamics and a new mechanism by which SXT/R391 ICEs can augment genome plasticity.